Petrogenesis of the drift magmatism in the Cabo Frio High, Campos Basin, Brazil: Evidence from Sr–Nd–Pb–Hf isotopes - Tatiele de Barros; Artur Corval; Sérgio de Castro Valente; Alan Wanderley Albuquerque Miranda (Brazilian Journal of Geology)
Abstract Situated between the Campos and Santos basins, the Cabo Frio High emerges as a focal point of heightened magmatic activity during the Santonian–Campanian and the Eocene period following the breakup of these basins. The geodynamic framework associated with these events took place during their passive margin stage, wherein magmatic occurrences could potentially be attributed to the reactivation of significant geological structures or thermal enhancement facilitated by proximal hotspots, within a context of lithospheric thinning (i.e., Trindade Plume). This investigation unveils novel Sr–Nd–Pb–Hf isotope data derived from alkaline magmatic rocks extracted from three boreholes strategically positioned within the Cabo Frio High area. The evolutionary trajectory of these rocks reflects the intricate processes of assimilation and fractional crystallization. The results of the analysis and binary mixing modeling point out to an involvement of both depleted (characterized by Depleted Mantle [DM]/Mid-Ocean Ridge Basalt [MORB] or HIMU compositions) and enriched (manifesting as the Enriched Mantle I [EMI] and the Enriched Mantle II [EMII]) sources in the genesis of these magmas. Moreover, the discerned incorporation of a fertile Ocean Island Basalt (OIB-like) reservoir hints at a plausible association with the Trindade Plume, amplifying the complexity of the magmatic genesis within the studied region.